Penerapan Strategi True or False Mata Pelajaran Fiqih untuk Meningkatkan Hasil Belajar Siswa Kelas VII MTs Al-Ikhwan Serapuh ABC - Arlina, Arlina; Maharani, Alya Wira (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The motif of this research is the lack of creativity of the seventh-grade fiqh teachers at MTs Al-Ikhwan Serapuh ABC in exploring learning models that can be used in the monotonous fiqh subject, causing students to get bored. Therefore, there needs to be a shift in the internal paradigm of teaching and learning strategies and the implementation of teacher-student interactions, implementing the right or wrong strategies in the process of teaching fiqh in the seventh grade at MTs Al-Ikhwan Serapuh ABC. The aim of this research is to answer whether the true or false strategy can improve students' learning outcomes about halal and haram food in the seventh grade at MTs Al-Ikhwan Serapuh ABC. This question is discussed in a classroom action research conducted over two cycles, each stage consisting of planning, action, observation, and reflection. The results show that the true or false strategy can improve students' learning outcomes in halal and haram food in the seventh grade at MTs Al-Ikhwan Serapuh ABC. This is reflected in the students' learning completeness per cycle, which is in the pre-cycle with a minimum passing grade (KKM) of 75 students pre-fap only 53.1%, in cycle I 65.3%, and in cycle II 85.6%.